A Child as a Donor for Hematopoietic Stem Cell Transplantation: Bioethical Justification—A Case Study on Sickle Cell Disease - Andrea Z. Pereira; Ricardo Hellman; Nelson Hamerschlak; Andrea Kondo; Polianna Mara Rodrigues de Souza; Wilson Leite Pedreira; Luiz Fernando Alves Lima Mantovani; Eduardo Juan Troster; Henrique Grunspun; Marco Aurélio Scarpinella Bueno (Case Reports in Hematology)
Hematopoietic stem cell transplantation (HSCT) is an important treatment option for children with severe and refractory sickle cell disease (SCD) with debilitating clinical complications. HSCT with cells from the bone marrow of a HLA-identical sibling used in SCD has a low mortality risk, high cure rate, and high event-free survival rate after a median follow-up of 5-6 years. However, matched donors are found in only about 20% of the patients. A boy aged 8 years with SCD had a sister, <2 years old, a fully compatible donor. The boy met all eligibility criteria to undergo HSCT, and he was suffering from cognitive and neurologic impairment due to ischemic events. A Bioethical Committee jointly discussed the ethical issues on this case after a pediatric evaluation released the very young sister for donation. The justification was that the sister would benefit from the donation too because of the greater likelihood of survival and cure and less suffering of her brother. The parents were informed about the risks and benefits for both children, and the family was psychologically evaluated. After their consent, HSCT was performed and the patient is cured from SCD. The complication for the donor was the need for blood transfusion.